Targeting insulin‐like growth factor‐1 receptor (IGF1R) for brain delivery of biologics - Alata, Wael; Yogi, Alvaro; Brunette, Eric; Delaney, Christie E.; Faassen, Henk; Hussack, Greg; Iqbal, Umar; Kemmerich, Kristin; Haqqani, Arsalan S.; Moreno, Maria J.; Stanimirovic, Danica B. (The FASEB journal, 2022)
The blood‐brain barrier (BBB) prevents the majority of drugs from crossing into the brain and reaching neurons. To overcome this challenge, safe and non‐invasive technologies targeting receptor‐mediated pathways have been developed. In this study, three single‐domain antibodies (sdAbs; IGF1R3, IGF1R4, and IGF1R5) targeting the extracellular domain of the human insulin‐like growth factor‐1 receptor (IGF1R), generated by llama immunization, showed enhanced transmigration across the rat BBB model (SV‐ARBEC) in vitro. The rate of brain uptake of these sdAbs fused to mouse Fc (sdAb‐mFc) in vivo was estimated using the fluorescent in situ brain perfusion (ISBP) technique followed by optical brain imaging and distribution volume evaluation. Compared to the brains perfused with the negative control A20.1‐mFc, the brains perfused with anti‐IGF1R sdAbs showed a significant increase of the total fluorescence intensity (~2‐fold, p < .01) and the distribution volume (~4‐fold, p < .01). The concentration curve for IGF1R4‐mFc demonstrated a linear accumulation plateauing at approximately 400 µg (~1 µM), suggesting a saturable mechanism of transport. Capillary depletion and mass spectrometry analyses of brain parenchyma post‐ISBP confirmed the IGF1R4‐mFc brain uptake with ~25% of the total amount being accumulated in the parenchymal fraction in contrast to undetectable levels of A20.1‐mFc after a 5‐min perfusion protocol. Systemic administration of IGF1R4‐mFc fused with the non‐BBB crossing analgesic peptide galanin (2 and 5 mg/kg) induced a dose‐dependent suppression of thermal hyperalgesia in the Hargreaves pain model. In conclusion, novel anti‐IGF1R sdAbs showed receptor‐mediated brain uptake with pharmacologically effective parenchymal delivery of non‐permeable neuroactive peptides.